Adhesive secretion in Schizolobium parahyba (Vell.) Blake (Leguminosae: Caesalpinioideae): histochemical and morpho-functional characterization of this unusual feature in woody plants - Paiva, Elder Antônio Sousa; Oliveira, Denise Maria Trombert; Canaveze, Yve; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2022)
The legume tree Schizolobium parahyba from the Brazilian Atlantic Forest shows young aerial organs covered with a sticky exudate. Aiming to clarify the functional aspects of the sticky secretions, we performed analyses on the dynamics of secretion through the plant development and characterized the chemical nature of the exudates by histochemical tests. We also studied the secretory tissue using light and electron microscopy. The production of the exudates starts soon after seed germination, being evident in the epicotyl but not in the hypocotyl and cotyledons. The secretory activity extends throughout the juvenile and pre-reproductive phase, in primary stems and leaf portions. After the first flowering, secretion was no longer observed. The lipid exudates are secreted by the epidermis and are composed of mixtures of essential oils and oleoresins. Modified plastids, extensive rough endoplasmic reticulum, proliferated smooth endoplasmic reticulum, enlarged vacuoles containing flocculant materials, membrane debris, and convoluted tubules/lamellae membranes covered with osmiophilic deposits are the main features of the secretory epidermal cells. Secretion exits the protoplast by exocytosis and accumulates in the cuticle, resulting in a sheath of concentric bands of electron-dense deposits, and is released by cuticle peeling. The hydrophobic nature of the secretion, which forms an impermeable layer on the epidermis of young organs, is a relevant attribute of the aerial organs of S. parahyba. In addition to protecting against desiccation, this exudate effectively captures particles and immobilizes insects and other arthropods.
Keywords: Protection attribute; Schizolobium parahyba; Secretory epidermis; Sticky exudate; Ultrastructure